2021
DOI: 10.3390/ijerph18178903
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Styles as a Moderator of the Association between Pubertal Timing and Chinese Adolescents’ Smoking Behavior

Abstract: Background: Pubertal timing refers to the timing of an individual regarding pubertal sexual maturation, both physiologically and psychologically. Existing research shows that pubertal timing is associated with behavioral problems. This study investigated the role of parenting style in the relationship between pubertal timing and Chinese adolescents’ smoking behavior. Methods: The study examined the association of pubertal timing, parenting style and adolescents’ smoking behavior, using the Pubertal Development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…Our results showed that the early pubertal timing was associated with poorer QOL in children and adolescents, which is similar to the results of the study of Japanese students by Fujimura et al [34]. Compared to previous studies [16,18,34], our study made some advances: First, this study used the PDS and the QOL scale for pubescent children to further explore the relationship between pubertal timing and the dimensions of QOL. Furthermore, our survey was conducted among students in grades 3 through 9 (8 to 15 years old), covering almost all age groups in early and middle adolescence.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results showed that the early pubertal timing was associated with poorer QOL in children and adolescents, which is similar to the results of the study of Japanese students by Fujimura et al [34]. Compared to previous studies [16,18,34], our study made some advances: First, this study used the PDS and the QOL scale for pubescent children to further explore the relationship between pubertal timing and the dimensions of QOL. Furthermore, our survey was conducted among students in grades 3 through 9 (8 to 15 years old), covering almost all age groups in early and middle adolescence.…”
Section: Discussionsupporting
confidence: 87%
“…The pubertal timing was evaluated using the total PDS score divided by the number of items. We defined three groups for pubertal timing: early (>mean + 1 SD for peers of the same age and sex), on time (within mean « SD), and late (<mean ¹ 1 SD) [16,30].…”
Section: Pubertal Timingmentioning
confidence: 99%
See 1 more Smart Citation
“…For the rst time, our study examined the association between parenting styles and youth's susceptibility to e-cigarette use and found that youth with father rejection were more likely to be susceptible to ecigarettes than youth with father emotional warmth. Our nding was in accordance with prior reporting that youth cigarette smoking was positively related to parental rejection and negatively related to parental emotional warmth [39]. According to the stress-coping model, parental styles with emotional warmth will enhance youth's ability to cope with stressful life events and prevent them from e-cigarette use [40].…”
Section: Parental Factorssupporting
confidence: 91%
“…Owing to the dual influence of traditional culture and political strategy [26,27], almost all parents attach great importance to the education and training of their children. Moreover, the inappropriate behavior of children is usually attributed to the parenting style employed by their parents [28,29]. Therefore, understanding the contradiction between modern medicine and tradition is a prerequisite for adopting correct dietary management measures.…”
Section: Discussionmentioning
confidence: 99%